Rancangan Sistem Pendukung Keputusan Pemilihan Calon Pegawai Honorer Pemerintah Kabupaten Lamandau Menggunakan Metode Profile Matching - Irmayanti, Ade; Rahmawati, Endah; Julita, Maya (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This study aims to design a Decision Support System (DSS) that implements the Profile Matching method for the selection of honorary employees in the Lamandau District Government. The often non-systematic selection process results in less objective decisions, necessitating a system that can enhance effectiveness and transparency in decision-making. The Profile Matching method is used to compare the profiles of candidates with predetermined criteria, leading to a fairer and more accurate selection process. Data were collected through interviews with relevant stakeholders in the Lamandau District Government, which were then analyzed to identify appropriate selection criteria. The findings indicate that the application of DSS can reduce subjectivity and improve clarity in the evaluation process. Additionally, the designed computer-based system facilitates faster data processing and presents information in a more comprehensible manner. Thus, this research is expected to make a significant contribution to the development of employee selection systems in local government and enhance the quality of human resources in public service. The implementation of information technology in DSS is anticipated to serve as a reference for future research in decision-making and human resource management.